2009
DOI: 10.1097/gim.0b013e318194ee8f
|View full text |Cite
|
Sign up to set email alerts
|

Array CGH in patients with learning disability (mental retardation) and congenital anomalies: updated systematic review and meta-analysis of 19 studies and 13,926 subjects

Abstract: Array-based comparative genomic hybridization is being increasingly used in patients with learning disability (mental retardation) and congenital anomalies. In this article, we update our previous meta-analysis evaluating the diagnostic and false-positive yields of this technology. An updated systematic review and meta-analysis was conducted investigating patients with learning disability and congenital anomalies in whom conventional cytogenetic analyses have proven negative. Nineteen studies (13,926 patients)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
134
1
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(164 citation statements)
references
References 51 publications
14
134
1
15
Order By: Relevance
“…This diagnostic yield is comparable to previous reports of historical RPC, which often used microarrays to assess these patients, and it is also consistent with the published literature on diagnostic yield in this patient population. 4,5,15 This study was originally designed to meet US Food and Drug Administration requirements and the interpreting cytogeneticist did not have access to any complementary information, as is standard in laboratory analysis (i.e., clinical data or supplementary laboratory testing). To obtain a more realistic view of CytoScan Dx Assay's diagnostic yield, it may be useful to reanalyze this data set with the complete laboratory information available to a qualified cytogeneticist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This diagnostic yield is comparable to previous reports of historical RPC, which often used microarrays to assess these patients, and it is also consistent with the published literature on diagnostic yield in this patient population. 4,5,15 This study was originally designed to meet US Food and Drug Administration requirements and the interpreting cytogeneticist did not have access to any complementary information, as is standard in laboratory analysis (i.e., clinical data or supplementary laboratory testing). To obtain a more realistic view of CytoScan Dx Assay's diagnostic yield, it may be useful to reanalyze this data set with the complete laboratory information available to a qualified cytogeneticist.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, with the advent of new techniques such as the chromosomal microarray (CMA), the yield has increased ~10-18%. 4,5 Additionally, it was recently reported by Shashi et al 6 that when a combination of laboratory tools including a microarray was used, 46% of patients suspected of having a genetic disease were diagnosed and 72% of these diagnoses were made on the first visit. The authors also showed that a genetic diagnosis in a patient leads to an average cost reduction of more than $1,435 in direct genetic laboratory tests (including number of visits to diagnosis and cost of all genetic tests performed) as compared with undiagnosed patients.…”
Section: Introductionmentioning
confidence: 99%
“…Four genomic gains were also identified (Tables 2 and 3; Patients [11][12][13][14]. Three of these were initially suspected to be novel and potentially pathogenic; the fourth gain (Patient 13; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis of 19 large, well-designed studies of intellectual disability and congenital anomalies reported a clinically significant range of 6 -35% for genomic imbalance and an overall diagnostic yield estimate of 10%. 11 This study included data from 13,926 patients (range 20 -8789/study), and although detailed age data are not reported in all studies, the studied population includes large populations from referral laboratories where sample ascertainment frequently comes from pediatricians and pediatric geneticists. One study of more than 5000 cases had a median age of just 4 years.…”
mentioning
confidence: 99%
“…1 A consequence of the untargeted nature of genomic tests is the increased likelihood of detecting an incidental finding (IF). The definition of an IF is variable, but in the context of genomic testing the term is used most commonly to describe a mutation that is detected but is unrelated to the original reason for testing.…”
Section: Introductionmentioning
confidence: 99%